NILAI-NILAI PENDIDIKAN KARAKTER DALAM FILM LASKAR PELANGI KARYA ANDREA HIRATA - Ahmad Fatah; Suci Herwani (Logat: Jurnal Bahasa Indonesia dan Pembelajaran, 2022)
ABSTRACK Laskar Pelangi (2008) is a film adapted from the novel Laskar Pelangi by Andrea Hirata. This film was directed by Riri Riza which was released on September 26, 2008. The screenplay was written by Salman Aristo. Laskar Pelangi film can be said to be an edutainment genre film because it conveys educational story messages that are packaged nicely. The film is also classified as a religious film because the background and values ​​presented are sourced from Islamic teachings. This research includes library research with a descriptive approach. Data sources are divided into two, namely primary data and secondary data. Primary data in the form of dialogue while secondary data in the form of supporting literature sources. Data collection techniques using documentation techniques. The data analysis technique is to analyze the contents of the dialogues of the characters. The problem raised is what character education values ​​are contained in the film Laskar Pelangi by Andrea Hirata and their relevance to commendable morals and human values. The expected goal is to analyze the values ​​of character education and their relevance to commendable morals and human values. The results showed that there were eight character education values ​​and their relevance to commendable morals and human values. The eight values ​​in question include tolerance, creativity, democracy, national spirit, respect for achievement, care for the environment, and social care. Keywords: Character Education Values, Praiseworthy Morals, Human Values